The BioRegio-contest: a new approach to technology policy and its regional consequences - Dirk Dohse (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
German technology policy has undergone a remarkable change during the last years. The first thing to mention is that technology policy in Germany takes a broader view now, focussing not only on knowledge creation (i.e. the invention process per se) but also on knowledge diffusion and faster commercialization. The second noteworthy change is the growing importance of regions as reference units for technology policy initiatives. The most prominent example is the BioRegio-contest initiated by the Federal Research Ministry in which 17 German regions compete for a given amount of public funding.The BioRegiocontest, its meaning for the German innovation system and some of its regional consequences are analyzed in this paper.
Keywords: H11; O14; O31; R42; 330; Biotechnische Forschung; Forschungs- und Technologiepolitik; Innovationspolitik; Forschungssubvention; Region; Business Network; Standortwettbewerb; Wirtschaftspolitische Wirkungsanalyse; Deutschland